Delayed flail chest from osteomyelitis and malnutrition that emerged 3 weeks after blunt chest trauma: a case report - Jin Bong Ye; Jin Young Lee; Junepill Seok (Journal of International Medical Research, 2024)
We present the case of a victim of a motor vehicle accident in his late 60s who suffered from severe torso injuries. He initially presented with abdominal and chest pain, and underwent emergency laparotomy for hemoperitoneum. After surgery, the patient developed pneumonia and septicemia, which were responsive to antibiotics. The patient was treated with mechanical ventilation in the intensive care unit for approximately 10 days and experienced a severe weight loss of approximately 30%, but slowly recovered without dyspnea. Notably, on hospital day 24, he experienced sudden respiratory distress and flail motion of the chest wall in a general ward. This late presentation of flail chest was attributed to non-union at rib fracture sites, and was likely exacerbated by malnutrition and osteomyelitis. Surgical stabilization of rib fractures and excision of the infected rib were successfully performed. The findings from this case highlight the complexity of managing delayed onset of flail chest. The findings from this case suggest the importance of vigilance for late emerging complications in patients with trauma, even when initial symptoms are absent.